Complete mitochondrial genome of the common Cuora (Cuora mccordi), China. Issue 7 (3rd July 2022) - Jiang, Hewei; Shen, Yawei; Wang, Hao; Zhao, Hailong; Chen, Xiaowu
Abstract: We report the complete mitochondrial genome of Cuora mccordi . The complete genome is a closed circular molecule of 16, 551 bp, with an overall base composition of 34.06% for A, 26.73% for T, 12.84% for G, and 26.37% for C. The A + T content is 60.79%. The full length consists of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one control region (D-loop). Phylogenetic analysis results showed that the mitogenome of Cuora mccordi was the closest to Cuora pani . The complete mitochondrial genome of Cuora mccordi (GenBank accession number: OM327796) can aid in understanding evolutionary relationships within Cuora .